Extraterrestrial organic matter and the detection of Life - Sephton,MA; Botta,O (SPACE SCI REV, 2008)
A fundamental goal of a number of forthcoming space missions is the detection and characterization of organic matter on planetary surfaces. Successful interpretation of data generated by in situ experiments will require discrimination between abiogenic and biogenic organic compounds. Carbon-rich meteorites provide scientists with examples of authentic extraterrestrial organic matter generated in the absence of life. Outcomes of meteorite studies include clues to protocols that will enable the unequivocal identification of organic matter derived from life. In this chapter we summarize the diagnostic abiogenic features of key compound classes involved in life detection and discuss their implications for analytical instruments destined to fly on future spacecraft missions.